Perilaku social loafing mahasiswa dalam mengerjakan tugas kelompok melalui sistem daring - Dinda Rutri Ayang Bestari MP; Siska Oktari; Rozi Sastra Purna (Jurnal Psikologi Tabularasa, 2022)
One of the learning methods provided during the online system is group assignments. But, group assignments which are expected to reduce the workload, without realizing it, can lead to social loafing behavior in students. Social loafing is a decrease in individual performance when working in groups, compared to when working alone. This study aims to get a Desccription of Social Loafing Behavior among Students of Andalas University in Doing Group Assignments through an Online System. This study uses descriptive quantitative methods with a sample of 347 Andalas University students, who meet certain criteria through purposive sampling technique. The measuring instrument used is a modification of the Social Loafing scale made by Purna, Armalita, and Oktari (2021), based on aspects of social loafing that have been proposed by Myers (2012), with a reliability coefficient of 0.972. The results showed that 72,3% or as many as 254 Andalas University students were in the medium category of social loafing. Based on the aspects of social loafing, the highest mean value is found in the aspect of widening of responsibilities, and the lowest mean value is in the aspect passivity. Salah satu metode belajar yang diberikan selama sistem daring adalah tugas kelompok. Namun tugas kelompok dapat memunculkan perilaku social loafing pada mahasiswa. Social loafing merupakan penurunan performa individu selama berkeja dalam kelompok, dibandngkan ketika bekerja secara sendiri. Tujuan penelitian ini ialah untuk melihat gambara perilaku social loafing pada mahasiswa Universitas Andalas dalam mengerjakan tugas kelompok melalui sistem daring. Penelitian ini menggunakan metode kuantitatif deskriptif dengan sampel sebanyak 347 mahasiswa Universitas Andalas yang memenuhi kriteria tertentu melalui teknik purposive sampling. Alat ukur yang digunakan adalah modifikasi dari skala Social Loafing yang dibuat oleh Purna, Armalita, dan Oktari (2021), berdasarkan aspek-aspek social loafing yang telah dikemukkan oleh Myers (2012) dengan koefisien reliabilitas 0,972. Hasil penelitian menunjukan bahwa gambaran perilaku social loafing pada mahasiswa Universitas andalas berada kategori sedang dengan persentase 73,3% atau sebnyak 254 responden. Berdasarkan aspek social loafing dengan nilai mean tertinggi yaitu pada aspek pelebaran tanggung jawab, dan nilai mean tererndah pada aspek sikap pasif.